Edukasi Bijak Dalam memilih Makanan di Aplikasi Pesan Antar pada Masa New Normal - Ratna Hamidah; Ratih Kurniasari; Linda Riski Sefrina; Sabrina Sabrina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
The fast-spreading Corona virus requires the government to take policies quickly to break the chain of its spread. Various ways are done starting from diverting all activities that are usually done offline to online. This increase in the use of technology is due to activity restrictions and causes people to spend more time at home, one of which is buying food online through delivery applications, resulting in many people choosing food without paying attention to the nutritional content contained in the food. Nutritional problems in adults tend to lead to obesity. One of the factors that influence nutritional status is nutritional knowledge. One of the prevention efforts that can be done is through education to increase public knowledge. This education is carried out online with the theme